Journal of Literary Semantics : An International Review (De Gruyter Mouton, 1972)
The Journal of Literary Semantics has pioneered and encouraged research into the relations between linguistics and literature. Widely read by theoretical and applied linguists, narratologists, poeticians, philosophers and psycholinguists, the journal publishes articles of a philosophical or theoretical nature that attempt to advance our understanding of the structures, dynamics, and significations of literary texts.